(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
The growing importance of environmental issues in Uzbekistan and worldwide has created an urgent need for a precise and accessible ecological terminology in the Uzbek language. Yet, while environmental discourse has expanded rapidly, the Uzbek lexicon has not kept pace, resulting in lexical gaps, inconsistent usage, and heavy reliance on foreign borrowings. This article draws on a qualitative review of 25 Uzbek-language environmental science textbooks, four bilingual glossaries, and 18 scientific papers published between 2020 and 2024 to identify and analyse five pressing challenges — the lack of equivalent terms, inconsistency and fragmentation, the rapid emergence of new concepts, the dominance of loanwords, and the difficulty of communicating technical terms to a broad audience. Concrete, step-by-step solutions are then proposed for each. By aligning linguistic planning with scientific accuracy and public comprehension, Uzbekistan can develop a coherent ecological lexicon suitable for education, policy, and research.